Techno-economic evaluation of integrated energy systems for heat recovery applications in food retail buildings. (1st January 2022) - Sarabia Escriva, Emilio José; Hart, Matthew; Acha, Salvador; Soto Francés, Víctor; Shah, Nilay; Markides, Christos N.
Highlights: Techno-economic analysis of low-carbon heat supply options for UK supermarkets. RIHC, an ASHP, and a thermal storage tank with advanced control is recommended. Best investments provide a 16-to-18-year payback without a carbon price. The UK renewable heat incentive subsidy (for ASHP) generates 89% of the 'savings' When a £100/tCO2e tax is considered, paybacks are reduced to a 9–11 years. Abstract: Eliminating the use of natural gas for non-domestic heat supply is an imperative component of net-zero targets. Techno-economic analyses of competing options for low-carbon heat supply are essential for decision makers developing decarbonisation strategies. This paper investigates the impact various heat supply configurations can have in UK supermarkets by using heat recovery principles from refrigeration systems under different climatic conditions. The methodology builds upon a steady-state model that has been validated in previous studies. All refrigeration integrated heating and cooling (RIHC) systems employ CO2 booster refrigeration to recover heat and provide space heating alongside various technologies such as thermal storage, air-source heat pumps (ASHPs) and direct electric heaters. Seven cases evaluating various technology combinations are analysed and compared against a conventional scenario in which the building is heated with a natural gas boiler. The specific combinations of technologies analysed here contrasts trade-offs and is a first in the literature. The capital costs of these projects are considered, giving insights into their business case. Results indicate that electric heaters are not cost-competitive in supermarkets. Meanwhile, RIHC and ASHP configurations are the most attractive option, and if a thermal storage tank system with advanced controls is included, the benefits increase even further. Best solutions have a 6.3% ROI, a payback time of 16 years while reducing energy demand by 62% and CO2 emissions by 54%. Such investments will be difficult to justify unless policy steers decision makers through incentives or the business case changes by implementing internal carbon pricing.